2014
DOI: 10.1155/2014/202983
|View full text |Cite
|
Sign up to set email alerts
|

Profile, Outcomes, and Determinants of Unsuccessful Tuberculosis Treatment Outcomes among HIV-Infected Tuberculosis Patients in a Nigerian State

Abstract: Background. Few studies have evaluated the rate of tuberculosis (TB)/human immunodeficiency virus (HIV) coinfection and the determinants of its treatment outcomes in Africa. We aimed to determine the predictors of unsuccessful treatment outcomes in HIV-infected tuberculosis patients in Nigeria. Methods. A retrospective cohort study design was used to assess adult TB/HIV patients who registered for TB treatment in two health facilities in Ebonyi State, Southeast Nigeria, between January 2011 and December 2012. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
6
22
5
Order By: Relevance
“…These findings compare favourably with the results of the similar survey studies on TB/HIV done in different tertiary institutions in Nigeria [15][16][17] ; and in Ethiopia 18 where worst treatment outcomes were found among the co-infected than those with TB disease only. Although several other factors may be contributory to the recorded unfavourable treatment outcomes among the TB/HIV infected patients, but the dual immune depressing diseases have been found to be the major culprits.…”
Section: African Health Sciences Vol 16 Issue 3 September 2016supporting
confidence: 84%
“…These findings compare favourably with the results of the similar survey studies on TB/HIV done in different tertiary institutions in Nigeria [15][16][17] ; and in Ethiopia 18 where worst treatment outcomes were found among the co-infected than those with TB disease only. Although several other factors may be contributory to the recorded unfavourable treatment outcomes among the TB/HIV infected patients, but the dual immune depressing diseases have been found to be the major culprits.…”
Section: African Health Sciences Vol 16 Issue 3 September 2016supporting
confidence: 84%
“…This pattern of high TB treatment success among new cases has been reported by several studies [25] [27] [28] [43]. Yet some others reported no significant effect on the treatment outcome by both the drug regimen used and the type of patient at diagnosis [19] [23] [41]. This report could likely be due to the fact that most category II patients are re-treatment cases and might have been long on the drugs leading to poor compliance to drugs, development of resistance to drugs and in turn poor treatment outcome.…”
Section: Discussionsupporting
confidence: 64%
“…This pattern of lower success rates among males has been supported by several studies, [7] [57]. Nevertheless one of the studies reported a higher burden among female patients while some others reported no effect of gender on TB treatment outcome [19] [41] [42] [52]. Gender differences in tuberculosis epidemiology may arise either as a consequence of differences in biological functioning or due to differences in the societal roles of men and women.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, other study in Nigeria found that male patients of TB/HIV co-infection either in rural or urban areas, contributed to successful TB treatment compared to female patients (19). Moreover, in the previous studies conducted among TB patients, female patients were found to have higher contribution to the unsuccessful of TB treatment (11,13).…”
Section: Discussionmentioning
confidence: 86%